Informed consent for peripheral nerve blocks at a tertiary level hospital in South Africa: a quality improvement project - Burger, Roxanne (Department of Anaesthesia and Perioperative Medicine, 2025)
Background: In South Africa, the doctrine of informed consent (introduced by the South African courts, Cape Provincial Division) dictates that all reasonable patients be told of material risks and alternative options before consenting to medical treatment or procedural interventions. The reasonable patient standard requires that a patient be told of all material risks that would influence a reasonable person in determining whether or not to consent to the treatment. Regional anaesthesia, including peripheral nerve blocks (PNBs), provides a plethora of benefits to patients undergoing surgery but, due to potential risks involved, also requires informed consent. Studies have shown that South African anaesthetists do not regularly obtain adequate informed consent for these procedures. We implemented a quality improvement project to facilitate and enhance documented informed consent in our setting. Methods: A prospective quality improvement project was established at Groote Schuur Hospital, Cape Town, including all PNBs performed in two-week blocks before and after the introduction of a standardised regional anaesthesia informed consent form. The primary outcome, comparing the incidence of documented informed consent between the two groups, was assessed with the McNemar paired-sample test for differences in proportions. Regression analysis was used to explore the effect of prespecified confounders (such as documented consent taken, benefits discussed, alternatives discussed, complications discussed and whether autonomy was documented). Results: In total, 39 and 43 patients were included in the pre- and post-intervention groups, respectively. In our setting, anaesthetists were 4.16 times (95% confidence interval (CI) -6.67 to -2.98, p < 0.001) more likely to take documented informed consent when provided with a standardised form. The incidence of documented informed consent improved from 7.7% to 60.5%. Regression analysis showed that these confounders influenced the recall of the PNB consent and discussed benefits and complications. Overall, recall was mostly influenced when benefits were discussed with patients (95%CI -20.023 to -14.64, p < 0.001). Conclusion: Documentation of informed consent for PNBs in our setting is poor. A standardised consent form can facilitate the documentation of consent significantly. Patient recollection of the consent process also improved, specifically when benefits were discussed.